A sulfur-rich segmental hyperbranched polymer as a coking inhibitor for endothermic hydrocarbon fuels. (1st March 2021) - Li, Shun; Guo, Yongsheng; Fang, Wenjun; He, Guijin
Graphical abstract: Highlights: A sulfur-rich hyperbranched polymer SHPGMA is prepared via the RAFT-SCVP method. SHPGMA is used as a coke inhibitor that can significantly reduce the filamentous coke. SHPGMA can passivate the metal sites on the pipeline to inhibit the catalytic coking. Abstract: A sulfur-rich segmental hyperbranched polymer, SHPGMA, is developed to inhibit the catalytic coking during the thermal cracking of hydrocarbon fuels. In this work, the SHPGMA with a narrow molecular weight range is prepared via the principle of reversible addition-fragmentation chain transfer polymerization. The decomposition of n- dodecyl in SHPGMA takes place firstly at about 170 °C, and the dissociation of the skeleton of SHPGMA occurred in the range from 290 to 500 °C, which indicates a wide onset temperature range. The cracking reactions of n- tridecane with or without SHPGMA under different conditions show that SHPGMA can inhibit the catalytic cracking of n- tridecane, which results in significant reduction of the catalytic coke, conversion and heat sink. With the function of SHPGMA, the filamentous coke deposited in the pipeline is significantly reduced, and the generated coke become incompact and small. The amount of coke per cracked n- tridecane decreases from 38.42 to 27.03 μg/g with the addition of 0.03 wt% SHPGMA-3. These results confirm the potential application of SHPGMA as the coke inhibitor to endothermic hydrocarbon fuels.